PERANAN BAURAN PEMASARAN DALAM MEMPENGARUHI KEPUTUSAN KONSUMEN MEMILIH HOTEL BINTANG 3 DI KOTA PALEMBANG - Stiawan, Mulkan (Jurnal Ilmu Manajemen, 2016)
This study aimed to determine the effect of marketing mix (hotel products, price, place, promotions, people, pshycal form) for the consumer’s decision choosing a 3 star hotel in the city of Palembang. There are two problem in this research, first wheater the marketing mix together significant effect on the consumer’s decision. Second marketing mix partially significant effect on the consumer’s decision.The data used in this study are primary data trought 125 respondent answer. Models of analysis used multiple linear regresion throught the instrument validity and reliability. Test charactistics data that is test of normality and linearity test. Test model consist of multicolinearity test and heterokesdatisitas test.Result of testing multiple linear regresion showed of hotel products, price, place, promotions, people, pshycal form together with influence on consumer’s decision, in partially hotel products, place, promotions, people, pshycal form have a positive influence on consumer’s decision. Price have not effect on consumer’s decision.Price doesn’t afeect consomer’s decision choosing a 3 star hotel because consumer’s do not know the rates set price hotel. Dominan consumer’s coming from institutions to participate in training, workshop, seminars, meeting etc.